Breast reconstruction: current and future options - Paul, Henry (Dove Medical Press, 2011)
When initiated by the devastating diagnosis of cancer, post ablative breast restoration has at its core the goal of restoring anatomic normalcy. The concepts of body image, wholeness, and overall well-being have been introduced to explain the paramount psychological influence the breast has on both individuals and society as a whole. Hence, a growing subspecialty has been established to recreate or simulate the lost breast. At least one third of breast cancer victims consider breast reconstruction. Breast reconstruction post mastectomy may be offered at the time of mastectomy or delayed post mastectomy after adjuvant therapy. This may be utilizing autologous tissues or implants and each has risks and benefits, especially when considering adjuvant therapy. In addition, there has been a move away from a traditional mastectomy to less invasive, but still curative procedures, such as skin-sparing and nipple-sparing mastectomy. These procedures provide the breast envelope to facilitate reconstruction. This paper reviews the primary issues in breast reconstruction, as well as their psychologic, oncologic, and social impact.